2013
DOI: 10.1007/s10995-013-1371-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Health and Health Care Systems for Children with Special Health Care Needs Using the Life Course Perspective

Abstract: To date, life course research in maternal and child health has largely focused on elucidating fetal and early life influences on adult health and less on promoting the health of children with special health care needs (CSHCN). Consideration of life course theory (LCT) for CSHCN is especially important given their increasing prevalence and comorbidity, their disproportionate vulnerability to weaknesses or instability in the health care system, and the growing evidence linking child and adult health and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 30 publications
1
48
0
2
Order By: Relevance
“…In the literature, there are several co-existent denominations for referring to these children, such as medically fragile children -referring to those that have serious health problems and frequently need technological devices to maintain their vital functions (3) , and children with medical complexity (CMC) -those that have multi-systemic disorders of a congenital or acquired nature, require intensive care and may be dependent on technological devices (4) . It is estimated that 15% to 20% of children in the United States up to the age of 17 have some special health need (5) . A study that aimed to estimate the number of medically fragile children, and the cost of their health services, showed that 0.25% of the children of the US State of North Carolina fitted this definition.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are several co-existent denominations for referring to these children, such as medically fragile children -referring to those that have serious health problems and frequently need technological devices to maintain their vital functions (3) , and children with medical complexity (CMC) -those that have multi-systemic disorders of a congenital or acquired nature, require intensive care and may be dependent on technological devices (4) . It is estimated that 15% to 20% of children in the United States up to the age of 17 have some special health need (5) . A study that aimed to estimate the number of medically fragile children, and the cost of their health services, showed that 0.25% of the children of the US State of North Carolina fitted this definition.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the importance of appropriate care across the health and education sectors, which is a stated responsibility of the medical home paradigm. 24 Our findings also point to providing care using a life course approach, 15,25 given that child and parent outcomes vary according to long-term SHCN profiles. One potential way to achieve this care is by implementing the overarching principles of the learning health care system.…”
Section: Discussionmentioning
confidence: 80%
“…11,12 There is currently limited knowledge about the natural history and variability over time of SHCN as a broad grouping and about how outcomes may vary by differing trajectories (eg, emerging, persistent), if such exist. 11 Newacheck et al 13,14 and, more recently, Bethell et al 15 have argued that this missing longitudinal information is crucial to inform the planning of medical, developmental, and education support services for these children across their life course.…”
mentioning
confidence: 99%
“…Horizontal integration refers to service coordination and systems integration not only within healthcare but also across multiple sectors-education, economic, and community development. And, longitudinal integration focuses on the continuum of care across the life course, especially across transition points [13,15,[18][19][20].…”
Section: From Isolated To Collective Impactmentioning
confidence: 99%